Repeat liver resection for colorectal metastases. Issue 7 (3rd May 2013) - Kulik, U.; Bektas, H.; Klempnauer, J.; Lehner, F.
<x xml:space="preserve">Abstract</x> Background Following resection of colorectal liver metastases (CLMs) up to 75 per cent of patients develop recurrent liver metastases. Although repeat resection remains the only curative therapy, data evaluating the outcome are deficient. This study analysed postoperative morbidity, mortality and independent predictors of survival following repeat resection of CLMs. Methods Data on surgical treatment of primary and recurrent CLMs between 1994 and 2010 were collected retrospectively, and compared with those for single hepatic resections carried out during the same period. Independent predictors of survival were evaluated by means of univariable and multivariable Cox regression models. Results In this interval 1026 primary resections of CLMs were performed and 94 patients underwent repeat CLM excision. Overall postoperative morbidity and mortality rates were low (15·8 and 1·3 per cent respectively), with no statistical difference in patients undergoing repeat surgery (P = 0·072). Compared with single liver resections, overall survival was improved in repeat resections (P = 0·003). Multivariable analysis revealed that size of primary CLM over 50 mm was an independent predictor of survival (hazard ratio (HR) 2·61; P = 0·008). Only major hepatic resection was associated with poorer outcome following repeat surgery (HR 2·62; P = 0·009). International Union Against Cancer stage, number of CLMs, age at surgery and need for intraoperative transfusion had no impact on survival after repeat resection. Conclusion Recurrent CLM surgery is feasible with similar morbidity and mortality rates to those of initial or single CLM resections.